Temperature distribution in rheumatoid hand after standard infrared treatment - Rutkowski, Radosław; Straburzyńska-Lupa, Anna; Korman, Paweł; Romanowski, Wojciech; Rąglewska, Patrycja; Konarska, Agata; Gizińska, Małgorzata; Hurnik, Elżbieta; Czubaszewski, Łukasz (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Comprehensive therapy of rheumatoid arthritis (RA), apart from pharmacological treatment, also necessitates an implementation of specialized procedures aimed at improving the mobility, stamina and strength of affected joints. Physical treatments used for the rehabilitation of patients with RA are most often related to thermal stimuli and change the temperature of the tissues. Each change of that kind is linked to the adequate vascular reaction and the changes in blood circulation within the affected area. Aim of the Study. The aim of this present study was to examine vascular changes in rheumatoid hand occurring as a physiological response to the mild thermal stimulus being applied, accounting for individual differences in its progress. Material and Methods. The research embraced 32 patients aged 54.9 ± 6.8 with diagnosed RA according to the standards of American College of Rheumatology. For physical therapy a conventional infrared lamp emitting A, B, C waves with a red colour filter was used. The area under treatment was the dorsal side of the hand. Each subject had eight thermographic pictures taken at the pre-defined time intervals: before the application, immediately after the application, and 5, 15, 30, 45, 60 and 120 minutes after the application. Results. The results were shown in a form of graphic reaction progress of the heated and unheated (contralateral) hand. Average static temperatures of both hands did not show any differences (31.8 ± 1.7°C – heated hand; 31.9 ± 1.8°C – unheated hand). Maximum temperature was obtained immediately following the IR lamp application: 35.0 ± 1.2°C for the heated hand and 32.2 ± 2.1°C for the unheated one. Among all analyzed diagrams showing reaction progress following IR application, four individual groups with the most similar results were formed. Conclusions. For all the patients in the study, a comparable decrease in tissue temperature initially increased by IR application was noted within the next 45 minutes following the application. No subject observed any undesirable reactions.
Keywords: rheumatoid hand; thermotherapy; microcirculation; concensual reaction